Taboo in traditional linguistic cultures (based on the yakut language and russian old-time dialects of yakutia) - Pavlova, Irina Petrovna; Gorbunova, Yana Yakovlevna (Revista EntreLinguas, 2021)
This paper is devoted to the study and analysis of the phenomenon of taboo in the traditional cultures of peoples living in the Arctic zone of Russia. The unique lexical material of the language of the Russian old-timers of the Arctic, reflecting the peculiarities of their worldview, is introduced into the scholarly discourse. The forbidden vocabulary and taboos on actions presented in the material under consideration cover, first of all, such language systems as the semantic fields "Hunting and fishing", "Disease", "Death" in a regular way. Due to the continuity of generations, in traditional cultures, many ancient prohibitions (maybe some in a distorted form) and ideas about them have survived to this day. The area of taboo reflects the features of the traditional life and management of peoples living in the Far North, serving as material for reconstructing fragments of the linguistic worldview. Este artículo está dedicado al estudio y análisis del fenómeno del tabú en las culturas tradicionales de los pueblos que viven en la zona ártica de Rusia. El material léxico único del idioma de los antiguos rusos del Ártico, que refleja las peculiaridades de su cosmovisión, se introduce en el discurso académico. El vocabulario prohibido y los tabúes sobre las acciones presentados en el material en cuestión cubren, en primer lugar, sistemas lingüísticos como los campos semánticos "Caza y pesca", "Enfermedad", "Muerte" de manera regular. Debido a la continuidad de generaciones, en las culturas tradicionales, muchas prohibiciones antiguas (tal vez algunas en forma distorsionada) e ideas sobre ellas han sobrevivido hasta nuestros días. El área de tabú refleja las características de la vida tradicional y la gestión de los pueblos que viven en el Extremo Norte, sirviendo como material para reconstruir fragmentos de la cosmovisión lingüística. Este artigo se dedica ao estudo e análise do fenômeno do tabu nas culturas tradicionais dos povos que vivem na zona ártica da Rússia. O material léxico único da língua dos russos ...